Pendampingan SDM Desa Wisata Garongan: Program Kerjasama Sekolah Tinggi Pariwisata AMPTA dengan Kementerian Pariwisata dan Ekonomi Kreatif/Badan Pariwisata dan Ekonomi Kreatif Tahun 2022 - Hary Hermawan; Arif Dwi Saputra; Prihatno; Nikasius Jonet Sinangjoyo; Hamdan Anwari; Hardi Wahyono; Amelia Lintang Mahiswara (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2022)
Assistance with human resources in the Garongan Tourism Village. Despite the abundance of potential tourism-related activities, the management of Garongan Tourism Village still has several flaws. The Yogyakarta AMPTA Tourism College, in partnership with the Ministry of Tourism and Creative Economy/Tourism and Creative Economy Agency, has established the Tourism Village Assistance Program in response to some current issues. The work programs that have been effectively put into practice include: (1) integrated tourist village FGD; (2) integrated tourism product packaging training; (3) integrated tour package sales training; (4) preparation of storytelling and edutrip guides for Garongan tourism village; (5) coaching for the preparation of tour packages; (6) training and coaching on digital tourism village marketing; (7) coaching of tourism village financial management; (8) tourism village scouting training; (9) Digitization of tour packages with audio-visual catalogues; (10) Special culinary training based on processed fish and salak; and (11) Training on making souvenirs with the theme of Garongan tourism village.